MINIMASI BIAYA PENGIRIMAN TAHU MENGGUNAKAN METODE TRANSPORTASI - Imam Arifin; Sandy Rahmansyah; Saarah Nur Fauziyyah; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2022)
Basically, all companies both big and small are always connected to the distribution of goods. The XYZ company is UMKM, the factory that is located at Ujung Berung, Bandung. The Company has three tofu factories that will distribute tofu into four different markets. This factory does not have a tofu flow distribution which results in high postage costs. In this study, the tofu flow distribution will be determined so that the cost of distributing tofu can be minimized. The method that can be used to determine the cost of distribution of tofu is the transportation method. The transportation methods used to solve the problems in this research are North West Corner (NWC), Least Cost and Vogel's Approximation Method (VAM) to determine the initial solution. Then optimized using the Stepping Stones method to get the minimum distribution costs. The calculation results obtained will be compared with the costs used by the previous company, with the hope that the results of this study can be considered by the company to be used in the tofu distribution